PROCESSOS DE FORMALIZAÇÃO-INFORMALIZAÇÃO NA FORMAÇÃO DE TILS BRASILEIROS E MEXICANOS: UMA ABORDAGEM SOCIOLÓGICA FIGURACIONAL - Costa Junior, Euluze Rodrigues da (2021)
This research aims to produce analyzes on the formalization-informalization processes that underlie the training of sign language translators and interpreters (TILS) in Brazil and Mexico. Conversations are elected as a procedure for the production/collection of data, considering the qualitative nature of the research in question, not to mention the assumptions of International Comparative Education assumed in this study. Then, more specifically, conversations with Brazilian and Mexican TILS were held in 16 virtual rooms organized on the Google Meet platform, which were recorded, transcribed and translated. This study is developed based on the assumptions of Figurational Sociology elaborated by the sociologist Norbert Elias (1993, 1994, 1995, 2001, 2014), taking as a contribution the notion of habitus and the formalizationinformalization sociodynamics. It is observed that the formation of TILS takes place in a plural and diverse perspective in view of the expansion of interdependence networks and the specialization of social functions that have taken place over time. Another important point concerns the fact that the charitable and assistencialist marks in the profession and performance of TILS are effects of the national habitus of the 20th century, as, but with tensions, they are associated with emancipatory movements with and/or deaf communities. It is also registered that, in the multiplicity of formative possibilities, these individuals have historically sought affirmation of their practices and intended - through discussions, assemblies, projects, among others - public policies around the profession, dissemination and valuation of sign languages. The engendered analyzes support the thesis that, at no historical moment, a final stage in the formations will be reached, since they are modeled in context, in the relationships with the other and before a dynamic forged in the processes of formalization-informalization interrelated with the national habitus of the respective time. The results of this work show that the formations of TILS in the investigated countries gained contours and impulses linked to the meanings attributed to TILS, sign languages, the deaf and the practices of translation and interpretation.